Extended Kalman filter-based state estimation of MOSFET circuit. Issue 6 (16th May 2019) - Bansal, Rahul; Majumdar, Sudipta
Abstract : Purpose: This paper aims to present the estimation of the output voltage of metal oxide semiconductor field effect transistor (MOSFET) using the extended Kalman filter (EKF) method. Design/methodology/approach: The method uses EKF for MOSFET output voltage estimation. To implement the EKF method, the state space model has been obtained using Kirchhoff's current law and Enz-Krummenacher-Vittoz model of the MOSFET circuit. Findings: The proposed method can be used for any mode of MOSFET operation besides near the quiescent point region. The nonlinearity that occurs in the saturation region of MOSFET can also be considered in the proposed method. The proposed method can also be used for a large input signal. Though Kalman filter can be used for the small amplitude input signal, it results in inaccurate estimation due to the linearization of the nonlinear system. Research limitations/implications: The method is able to track the parameters when they are slowly changing with time. Originality/value: The proposed method presents maximal precision of simulation as the maximal precision of simulation requires modeling of the circuit in terms of device parameters and circuit elements.